FROM TOPONYMS TO TEXTILES NAMES IN PORTUGUESE: CONTRIBUTIONS TO HISTORY OF THE TEXTILE LEXICON - Bernardo, Jozimar Luciovanio [UNESP]; Rezende, Rayne Mesquita de [UNESP] (Univ Fed Goias, Campus Catalao, 2019)
In this article, we have selected six textiles names coming from toponyms, inventoried from the corpus of the Dicionario Historico do Portugues do Brasil - Seculos XVI, XVII e XVIII, in order to investigate whether such lexical units necessarily indicate the origin of the fabrics or if there were other facts / motivations involved in the denomination processes. We consulted the meanings of each word from old and current Portuguese dictionaries, and we also use foreign language dictionaries, etymologies, glossaries, monographs, etc. to complement and substantiate the analyses. We understand that the denominations don't merely indicate the place of origin of the fabric manufacture, as they may indicate the place of diffusion. The referential importance that toponyms have acquired through a product, for example, makes them likely to be borrowed to name it, so that context, value, and notoriety of the product are related to names.
Keywords: Fabrics; Vocabulary; Dictionary; Toponyms; DHPB